Water and Politics - Herrera, Veronica (University of Michigan Press, 2024)
Most of the world’s population lives in cities in developing countries, where access to basic public services, such as water, electricity, and health clinics, is either inadequate or sorely missing. Water and Politics shows how politicians benefit politically from manipulating public service provision for electoral gain. In many young democracies, politicians exchange water service for votes or political support, rewarding allies or punishing political enemies. Surprisingly, the political problem of water provision has become more pronounced, as water service represents a valuable political currency in resource-scarce environments.